Influential Marketing Strategies are Simultaneously Against the (use of) the Occupational Hospitalization by the BPJS Patients in Hospital Muhammadiyah University of Malang - Arief Churniawan; Byba Melda Suhita; Yuly Peristiowati (Journal for Quality in Public Health, 2020)
The aimed of this research to analyze marketing strategies take effect simultaneously against the (use of) the occupational hospitalization by the BPJS patients in hospital Muhammadiyah University of Malang. Quantitative research design that is crossectional. Research on variable i.e. the influence marketing strategies are simultaneously against and as the independent variable and the (use of) occupation hospitalization as the dependent variable BPJS. Population research i.e. whole health BPJS patients who underwent hospitalization on 15th October – November 15, 2018. Samples taken by random sampling technique as much as 92 respondents. The data collected by the instruments and questionnaires processed in coding, editing, tabulating and scoring as well as tested with linear regression test. Linear regression results indicate that partially and the simultaneous there are shows a value of p = 0,00 < 0.05 so that ther is influence marketing strategies towards occupational (usage) of inpatient care by patients BPJS RS UMM Malang. R Square (R2) of 0.660 or 60.6% that shows contributions from independent variable marketing strategies (product, price, place, people, and processes), while the rest was 39.4% in influence by other factors that do not exist in this research model. Multiple correlation coefficient is used to measure the keeratan relationship between the dependent and independent variables. The results showed that the strategy of marketing (product, price, place, people, and processes) conducted by the managing of RS UMM exactly will affect the increase in occupasi or DRILL the patients. Process management efekstif, efficient and does not kink as well as facilitate the patient in obtaining health services can be one alternative reference patient in taking a decision to receive a health service. The existence of a negative perception by the patient about marketing strategy indicated that dissatisfaction received the patient and can make patients feel uncomfortable in accepting hospital service, so this affects patients in using the services of the hospital or hospital can move patients